Surface Charge Density Inside a Silicon Nitride Nanopore - Lin, Kabin (Langmuir : the ACS journal of surfaces and colloids, 2021)
Surface charges inside a nanopore determine the zeta potential and ion distributions and play a significant role in affecting ion transport and the sensitivity of detecting biomolecules. It is of great importance to study the fluctuation of surface charges with the salt concentration and pH in various applications of nanopores. Herein, we proposed a theoretical model to predict the surface charge density of a Si3N4 nanopore, in which both silanol and amine groups were taken into account. It was demonstrated that the surface charge density in the Si3N4 nanopore changes not only with pH but also with the salt concentration. The theoretical model could well predict the experimental results with different salt concentrations, pH values, and pore sizes. The effect of surface functional groups on the isopotential point (pHiep) of the Si3N4 nanopore was also systematically studied. The results indicated that the silanol groups are major determinants of the surface charge, but the influences of the amine groups should not be ignored because the small number of amine groups can change pHiep dramatically. The pHiep value of the Si3N4 nanopore was measured as 4.1, and the ratio of amine over silanol was ascertained as 0.013